The impact of a professional development model on middle school science teachers' efficacy and implementation of inquiry. Issue 18 (11th December 2016) - Lotter, Christine; Smiley, Whitney; Thompson, Stephen; Dickenson, Tammiee
ABSTRACT: This study investigated a professional development model designed to improve teachers' inquiry teaching efficacy as well as the quality of their inquiry instruction through engaging teachers in practice-teaching and reflection sessions. The programme began with a two-week summer Institute focused on both inquiry pedagogy and science content and continued with academic year support for participants' inquiry implementation. An inquiry teaching efficacy instrument was administered 3 times to 25 teacher participants to gauge changes in their personal self-efficacy and outcome expectancy across 5 essential features of classroom inquiry. To examine actual practices, pre/post classroom observations of the teachers' inquiry enactments were evaluated using a quality of inquiry observation protocol. Following the summer Institute, teachers had statistically significant increases in their self-efficacy for teaching inquiry in four of the five essential features and increases in one of the five essential features for outcome expectancy. Teachers' quality of inquiry teaching also increased after the professional development programme. We discuss implications of this PD model for moving teachers towards implementation of new instructional techniques as well as the influence of a supportive school community on teachers' efficacy with inquiry instruction.